The relevance of household contacts tracing among child contacts of patients with multidrug-resistant tuberculosis - O. M. Raznatovska; A. S. Moskaliuk; T. A. Grekova; L. I. Chernyshova; O. O. Pushnova; T. I. Shelestina (Civic Union "Communicable Diseases Intensive Care Association", 2020)
BACKGROUND. The World Health Organization (WHO) reports an unknown contact history of pediatric tuberculosis (TB), especially in children younger than 5 years old. Tracing pediatric household contacts of patients with multidrug-resistant TB (MDR-TB) is considered to be a highly effective intervention for detection of new cases of chemoresistant TB in children and timely prevention of its transmission. OBJECTIVE. To study the nature of TB process manifestations and concordance of mycobacterium tuberculosis (MBT) drug resistance profiles in household child contacts of patients with MDR-TB. MATERIALS AND METHODS. The nature of TB process manifestations and concordance of MBT drug resistance profiles in 12 household child contacts of patients with MDR-TB in 6 households (6 adult MDR-TB index patients, IP) were studied. Adults and children were examined and treated in the Pulmonary Tuberculosis Department No 3 and in the Pediatric Department of the Clinical Base of the Department of Phthisiology and Pulmonology of Zaporizhzhia State Medical University at the Municipal Institution "Zaporizhzhia Regional Tuberculosis Clinical Dispensary". RESULTS AND DISCUSSION. The tracing of children who were household contacts of the MDR-TB IP revealed the following features. The incidence of child TB was 2 times higher than that of contact adults (44 % vs. 20 %). Moreover, the incidence among children younger than 2 years of age was almost 3 times higher than in children across other age groups (54.5 % vs. 18.2 % in children younger than 5 years of age and 18.2 % in children aged 5 years and older). The children were non-BCG vaccinated in 63.6 % of cases. There was an alarmingly high rate of non-BCG vaccinated children, namely 83.3 % among individuals younger than 2 years of age and all of those younger than 5 years of age (100 %). The children mostly presented small clinical forms of non-destructive TB: intrathoracic lymph node TB (36.4 %), MBT complex (36.4 %) and focal TB (18.2 %). Most of the children (63.6 %) who developed TB were detected within the first year of IP with MDR-TB follow-up, and it is worthy of note that in the majority of cases (4 households; 66.6 %). With respect to the concordance of MBT drug resistance profiles between the children and MDR-TB IP in the households, diagnosis in children was microbiologically confirmed in only 3 cases (3 households) demonstrating the complete concordance of profiles in each one. At the same time, the complete concordance of MBT drug resistance profiles between adult household contacts and the MDR-TB IP was also recorded in 3 cases. As is evident, across the household contacts group aged between 0 and 18 years who were exposed to the MDR-TB IP, the most susceptible to develop TB were non-BCG vaccinated children younger than 2 years. More worryingly is that among 3 microbiologically conformed individuals of this age group, 2 children younger than 2 years were found to have their own drug resistant MTB isolates. CONCLUSIONS. Tracing household child contacts of MDR-TB IP is particularly effective for timely detection of active TB within the first year of MDR-TB IP follow-up. Non-BCG vaccinated children younger than 2 years of age are at the highest risk for MDR-TB followed by non-BCG vaccinated children younger than 5 years of age. The early detection and timely antimycobacterial therapy initiation based on drug susceptibility test results of a MDR-TB IP is a guarantee not only for an effective treatment but also for a reduction in the MDR-TB transmission to other persons.